2020
DOI: 10.1103/physrevresearch.2.023142
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-gap response of type-I noncentrosymmetric BeAu superconductor

Abstract: Precise measurements of the thermodynamic critical field (Bc) in type-I noncentrosymmetric superconductor BeAu were performed by means of the muon-spin rotation/relaxation technique. The temperature evolution of Bc can not be described within the single gap scenario and it requires the presence of at least two different types of the superconducting order parameters. The selfconsistent two-gap approach, adapted for analysis of Bc(T ) behavior, suggests the presence of two superconducing energy gaps with the gap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 60 publications
6
40
0
Order By: Relevance
“…27,28 However, a more comprehensive analysis of the superconducting state in Y 4 Be 33 Pt 16 is currently underway. In particular, because several in-depth muon spin-rotation, relaxation, and resonance experiments performed on another Be-containing non-centrosymmetric superconductor BeAu 24 revealed that not only type-I character, 29 but also a multi-gap nature of superconductivity 30 may exist in such unconventional systems.…”
Section: Resultsmentioning
confidence: 99%
“…27,28 However, a more comprehensive analysis of the superconducting state in Y 4 Be 33 Pt 16 is currently underway. In particular, because several in-depth muon spin-rotation, relaxation, and resonance experiments performed on another Be-containing non-centrosymmetric superconductor BeAu 24 revealed that not only type-I character, 29 but also a multi-gap nature of superconductivity 30 may exist in such unconventional systems.…”
Section: Resultsmentioning
confidence: 99%
“…1), the measured B c (T ) dependences should be analyzed within the multigap scenario. Such an approach was recently used by us to describe the two-gap superconductivity in noncentrosymmetric binary alloy AuBe [18,19]. However, as will be shown later, in elemental Pb, the single-gap approach was found to describe the experimental data reasonably precisely, so any type of admixture of the second superconducting en-ergy gap was not expected [see also the single-gap theory curves in panels (a) and (b) of Fig.…”
mentioning
confidence: 98%
“…[B c (0) = B c (T = 0), N F (0) is the density of states at the Fermi level, and is the zero-temperature value of the superconducting energy gap], becomes a direct probe of multiple superconducting energy gaps [16][17][18][19], as well as allows one to probe the superconducting gap anisotropy [20][21][22]. As the temperature dependence of B c normalized to its zerotemperature value follows very closely a nearly quadratic * rustem.khasanov@psi.ch behavior, the deviation function D(T ) is normally considered:…”
mentioning
confidence: 99%
See 2 more Smart Citations